Peran Wakaf Terhadap Ekonomi Islam di Era Pandemi Covid-19 - Muhammad Aulia Fajri (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2022)
The COVID-19 pandemic has an impact on all aspects of life, such as in the economic, health, education and socio-cultural sectors. In the economic sector, the most affected are the lower middle class. While a stabilization package is needed to minimize the impact of Covid 19. Here Waqf acts as a useful stabilizing tool to minimize the impact of Covid 19. Waqf is one of the solutions offered by the Islamic social finance sector in the face of a crisis. in an effort to generate strong demand. in parallel, it will generate a demand (offer) that will gradually restore the balance of economic transactions in society.